Canine olfactory detection of florfenicol residues in goat milk: a pilot study - Clapham, Maaike O.; McElroy, Dierdra; Mercer, Melissa A.; Kass, Philip H.; Tell, Lisa A. (Frontiers in Veterinary Science, 2025)
IntroductionCanine olfaction has been used to detect drug residues across a variety of matrices as part of law enforcement efforts. As such, canine olfactory sample screening should hold promise as a potential tool for detecting drug residues in food products to support human food safety in resource limited settings or where sensitive analytical methods are not available for various matrices. The objective of this pilot study was to evaluate the ability of companion dogs undergoing low-frequency olfactory detection training to detect florfenicol and its metabolite, florfenicol amine (FA), in incurred residue goat milk samples.MethodsCompanion dogs (n = 8) of various breeds with prior odor detection experience were enrolled in a canine odor detection study for 9 weeks to detect florfenicol/FA that entailed once weekly testing sessions. Double-blinded testing was performed in two phases. Study phase 1 consisted of 11 florfenicol/FA-contaminated goat milk samples (combined [florfenicol + FA] concentrations ranging from 17.44–1443.30 ppb) with 2 distractors, items that might distract the dog while working, per run presented to n = 8 dogs. For study phase 2, the highest performing dogs (n = 3) from study phase 1 were tested with low concentration (<20 ppb) samples (n = 11) that were identified as being positive using a rapid residue detection test. Performance metrics, including accuracy, sensitivity, and specificity, were assessed across sample drug concentration categories.ResultsFor study phase 1, mean detection accuracy, sensitivity, and specificity were 0.80 [95% confidence interval (CI) (0.74–0.86), 0.70 (95% CI 0.65–0.76), and 0.86 (95% CI 0.82–0.88)], respectively. Sensitivity increased with higher drug concentrations, ranging from 0.38 at 17.96 ppb to 0.96 at 1443.30 ppb. Study phase 2 accuracy, sensitivity, and specificity were 0.88 (95% CI 0.85–0.91), 0.82 (95% CI 0.73–0.88), and 0.91 (95% CI 0.86–0.94), respectively. False positives were most often associated with blank goat milk.DiscussionCompanion dogs undergoing low-frequency olfactory odor detection training were able to detect florfenicol/FA residues in goat milk with high specificity, particularly at high concentrations. However, sensitivity at low concentrations was limited. While canine olfactory detection does not appear to be suitable as a confirmatory method for companion dogs with low training commitments, this pilot study demonstrates its potential as an initial screening tool, particularly in resource-limited settings. Future research is needed to refine training protocols and assess performance under field conditions.